Patrimonio, cultura material y diferenciación social en la ciudad de Soria durante el siglo XVIII - Ana Isabel Sanz Yagüe (Nuevo mundo - Mundos Nuevos, 2008)
Nowadays, the material bases of social inequality require the acknowledging of the assets and social factors as interdependent concepts. Soria, a small town in the north of Castile, has not yet been studied from this perspective, for which we are compelled to present here preliminary aspects such as the distribution of wealth and household incomes in the mid-eighteenth century. This short period permit us to combine two important sources: The cadastre of Ensenada and several partition requests. These sources have revealed an extreme concentration of real estate and livestock, and also well defined patrimonial categories.